Poly(ADP-ribose) synthesis, a marker of granulocyte differentiation. - Ikai, K (1980)
By using an indirect immunofluorescence technique, the distribution of poly(ADP-ribose) synthesis in human blood cells was investigated. The antibody used was reactive with poly(ADP-ribose) larger than trimers. The specific immunofluorescence of poly(ADP-ribose) synthesized in situ from NAD+ was observed in nuclei of lymphocytes and monocytes in normal peripheral blood. No immunofluorescence, however, was detected in granulocytes and erythrocytes. In agreement with this finding, no incorporation of radioactivity from [adenine-14C]NAD+ into acid-insoluble material was detectable in nuclei isolated from granulocytes. In normal bone marrow, the immunofluorescence of poly(ADP-ribose) was not observed in myelocytes or in their descendants but was observed in nuclei of lymphocytes and erythroblasts. Myelocytes and mature granulocytes in peripheral blood as well as in bone marrow of patients with chronic myelocytic leukemia were totally negative in the polymer-specific immunofluorescence. In marked contrast, prominent fluorescence was observed in nuclei of myeloblasts that appeared in peripheral blood as well as in bone marrow of patients with acute myeloblastic leukemia. Myeloblasts appearing in peripheral blood of patients in blastic crisis of chronic myelocytic leukemia also showed the nuclear immunofluorescence. These results suggest that the capacity for synthesizing poly(ADP-ribose) serves as a marker of differentiation of granulocytes, and its immunohistochemical analysis may be useful for differential diagnosis of leukemias, especially in blastic crisis.